DOI: 10.1007/978-3-540-70970-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tessellation Metaphors in the Display of Geographical Uncertainty

Abstract: This paper explores in detail a new and effective metaphor for visualising choropleth map uncertainty. The "level-of-detail" metaphor has been shown here to communicate attribute uncertainty, but also spatial uncertainty as a secondary expression. The metaphor is delivered to the map viewer via the regular tessellated output of the Hexagonal or Rhombus (HoR) quadtree spatial data structure, as a semi-transparent map layer that lies on top of the choropleth (termed the trustree when used in this manner). For te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Similar to the work we present here, a number of studies by Kardos and colleagues evaluate a technique called 'trustree' that depicts uncertainty in census maps by varying the level of detail locally (Kardos et al 2007;Kardos et al 2008). They found that the visual metaphor of 'detail', i.e., a coarser grid in uncertain areas is more usable than a metaphor of 'clutter' that represents uncertain areas with a finer grid.…”
Section: Related Worksupporting
confidence: 52%
“…Similar to the work we present here, a number of studies by Kardos and colleagues evaluate a technique called 'trustree' that depicts uncertainty in census maps by varying the level of detail locally (Kardos et al 2007;Kardos et al 2008). They found that the visual metaphor of 'detail', i.e., a coarser grid in uncertain areas is more usable than a metaphor of 'clutter' that represents uncertain areas with a finer grid.…”
Section: Related Worksupporting
confidence: 52%
“…Expertise is described in many ways that are usually not directly comparable across studies, e.g. experience in using geographic information (Gerharz and Pebesma, 2009;Kardos et al, 2008), experience with the concept of uncertainty and its visualisation (Kardos et al, 2008;Kinkeldey et al, 2014), experience in maps and mapping (Evans, 1997, MacEachren et al, 2012, training or knowledge in the application domain (Aerts et al, 2003;Kolbeinsson, 2013;Kunz et al, 2011;Senaratne et al, 2012) or computer literacy more generally (Newman and Lee, 2004). Self-assessment was often used to determine the subjects' expertise, especially when participants were recruited via the web (Aerts et al, 2003;Kinkeldey et al, 2014;Senaratne et al, 2012).…”
Section: Participantsmentioning
confidence: 99%
“…For example, altering the spacing and size of repeated point and/or line symbols adds visual complexity to a surface in the form of a texture. Such provision of detail can act as a visual metaphor for uncertainty (where more detail means more certainty -Kardos, Moore, and Benwell 2008). The colour-based variables can represent qualitative attributes, such as hue being used to distinguish one project from another (though terrain does a good job of this).…”
Section: Extending Spatial Expression With Cartographic Variablesmentioning
confidence: 99%